2022
DOI: 10.1186/s42238-022-00126-z
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro effect of delta-9-tetrahydrocannabinol and cannabidiol on whole blood viscosity, elasticity and membrane integrity

Abstract: Background The main biological activities of cannabis are due to the presence of several compounds known as cannabinoids. Delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) are two of the main cannabinoids. Studies have shown that the effects of THC can be modulated by CBD. Objective This study aims to look at the effect of different concentrations of THC and CBD separately and in combination, on blood viscosity, elasticity and membrane integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…From this aspect, it appears that alone or the combination of two mechanisms can describe the lipophilic actions of cannabinoids ( Oz, 2006 ; Oz et al, 2014 ; Ghovanloo and Ruben, 2021 ). First, cannabinoids, like other lipophilic molecules, partition into the lipid bilayer and alter the biophysical properties of the membrane by reducing membrane electrical resistance ( Bach et al, 1976 ), increasing membrane fluidity ( Hillard et al, 1985 ; Mavromoustakos et al, 2001 ; Dainese et al, 2012 ), changing membrane order ( Bloom et al, 1997 ), increasing membrane stiffness ( Ghovanloo et al, 2021 ; Ghovanloo and Ruben, 2021 ), increasing membrane elasticity ( Medeiros et al, 2017 ; James et al, 2022 ), and changing physicochemical and structural properties of bilayer membranes ( Makriyannis et al, 1990 ; Yang et al, 1992 ; Ambrosi et al, 2005 ; Tiburu et al, 2007 ; Tian et al, 2011 ). Secondly, cannabinoids can bind directly to transmembrane domains of ion channels embedded in the cell membrane ( Xiong et al, 2011a ; Xiong et al, 2012b ; Lu et al, 2018 ; Ghovanloo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…From this aspect, it appears that alone or the combination of two mechanisms can describe the lipophilic actions of cannabinoids ( Oz, 2006 ; Oz et al, 2014 ; Ghovanloo and Ruben, 2021 ). First, cannabinoids, like other lipophilic molecules, partition into the lipid bilayer and alter the biophysical properties of the membrane by reducing membrane electrical resistance ( Bach et al, 1976 ), increasing membrane fluidity ( Hillard et al, 1985 ; Mavromoustakos et al, 2001 ; Dainese et al, 2012 ), changing membrane order ( Bloom et al, 1997 ), increasing membrane stiffness ( Ghovanloo et al, 2021 ; Ghovanloo and Ruben, 2021 ), increasing membrane elasticity ( Medeiros et al, 2017 ; James et al, 2022 ), and changing physicochemical and structural properties of bilayer membranes ( Makriyannis et al, 1990 ; Yang et al, 1992 ; Ambrosi et al, 2005 ; Tiburu et al, 2007 ; Tian et al, 2011 ). Secondly, cannabinoids can bind directly to transmembrane domains of ion channels embedded in the cell membrane ( Xiong et al, 2011a ; Xiong et al, 2012b ; Lu et al, 2018 ; Ghovanloo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another in vitro experiment reported that CBD extract in combination with THC significantly increased the elasticity of blood cells ie, RBC morphology and membrane integrity. 2 Moreover, clinical trial data had shown that topical application of CBD-enriched ointment without THC significantly improved skin elasticity. 23 Our results showed that CBD significantly improved elasticity in rat cardiomyoblast cell line (H9C2) at various concentrations.…”
Section: Effect Of Cbd On Mitochondrial Function -Atp Synthesismentioning
confidence: 99%
“…One of the clinical trial data reported that CBD increased red blood cell viscosity and elasticity. 2 CBD has potent anti-inflammatory, 3 immunomodulatory, and analgesic effects through activating cannabinoid-1 and − 2 (CB1 and CB2) receptors. CBD treatment also reduced the production of cytokines in an animal model of chronic asthma, inflammatory lung diseases, etc.…”
Section: Introductionmentioning
confidence: 99%